Integrative Multi‐Omics Approaches Reveal Selectivity Profiles and Molecular Mechanisms of FIIN‐2, a Covalent FGFR Inhibitor - Ying Fu; Dandan Zhu; Xiaojuan Chen; Lingzhi Qu; Ming Guo; Shuhong Zhang; Guangyu Xu; Zhuchu Chen; Maoyu Li; Yongheng Chen (Advanced Science)
Abstract Fibroblast growth factor receptor (FGFR) inhibitors are emerged as an important class of targeted therapies in oncology, targeting key pathways associated with tumor growth, angiogenesis, and resistance to conventional treatments. FIIN‐2, the first irreversible covalent pan‐FGFR inhibitor, has shown promise in overcoming resistance due to gatekeeper mutations; however, its selectivity and molecular mechanisms in tumors remain poorly understood. In this study, an FIIN‐2 chemical probe is designed and synthesized to identify both established and novel targets in hepatocellular carcinoma (HCC) via chemoproteomic profiling. An integrative multi‐omics approach, including chemoproteomic, phosphoproteomic, transcriptomic, and proteomic analyses, is utilized to elucidate the full spectrum of target proteins, signaling pathways, and downstream effectors regulated by FIIN‐2 in HCC. Notably, adenosine monophosphate‐activated protein kinase α1 (AMPKα1) is identified as a novel target of FIIN‐2, with Cys185 identified as its covalent binding site. These findings reveal that FIIN‐2 can induce autophagy by directly binding to and activating AMPKα1, influencing its anti‐tumor activity in HCC cells. Overall, this study greatly advances the understanding of FIIN‐2′s on‐ and off‐target effects, offering a comprehensive view of its molecular mechanisms in cancer cells. The integrative multi‐omics approach provides a valuable framework for the development and optimization of covalent kinase inhibitors.